2019
DOI: 10.1016/j.tmp.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Price-setting behavior in a tourism sharing economy accommodation market: A hedonic price analysis of AirBnB hosts in the caribbean

Abstract: This study investigated the price-setting behaviour of hosts in the tourism sharing economy in the Caribbean. Generally speaking, we find that site, reputation, convenience, personal and amenities attributes, along with country-level indicators significantly affect prices in the Caribbean. More specifically, most attributes have a positive effect on price-setting. Larger accommodations charge higher prices. Hosts with superior reputations charge higher prices. However, listings with a larger number of ratings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 48 publications
1
27
0
5
Order By: Relevance
“…Gibbs et al, 2018;Guttentag & Smith, 2017;Wang & Nicolau, 2017;Xie & Kwok, 2017), mainly aff ecting two and three-star traditional hotels at destination. Airbnb's market share presents a diverse off er of accommodations, consisting of super-host, multi-listing host, and single-listing host lodgings, mostly belonging to one existing host (DiNatale et al, 2018;Lorde et al, 2019), with traditionally a higher rent for private rooms than for entire houses. On the other hand, Adamiak (2018) showed that the diff erence between the rent of rooms, houses, and apartments is primarily based on the destinations' level of tourist attractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibbs et al, 2018;Guttentag & Smith, 2017;Wang & Nicolau, 2017;Xie & Kwok, 2017), mainly aff ecting two and three-star traditional hotels at destination. Airbnb's market share presents a diverse off er of accommodations, consisting of super-host, multi-listing host, and single-listing host lodgings, mostly belonging to one existing host (DiNatale et al, 2018;Lorde et al, 2019), with traditionally a higher rent for private rooms than for entire houses. On the other hand, Adamiak (2018) showed that the diff erence between the rent of rooms, houses, and apartments is primarily based on the destinations' level of tourist attractions.…”
Section: Discussionmentioning
confidence: 99%
“…Th e innovative element of Airbnb is the off ering via Internet of short-to long-term lodging to tourists (Lorde, Jacob, & Weekes, 2019) sharing at low cost private rooms, apartments or homes, randomly available in the society. Airbnb's sharing model is disruptive compared to the classical way tourist have been lodged in hotels, a system applied for decades (Guttentag, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, several publications point to hedonistic motives as an important factor for online shopping (Parsons 2002, Wolfinbarger andGilly 2003). Not in vain, the study focused on Airbnb in the Caribbean found that, among others, convenience, personal and amenities services, significantly affect prices (Lorde et al 2019). Additionally, and according to Guttentag (2019), Airbnb offers an alternative value proposition to guests centered around the potential for a more authentic local experience (hedonism).…”
Section: Antededents Of Non-monetary Pricementioning
confidence: 99%
“…Variables related to the price include the environment, the social aspect, the accessibility, and the spillover impacts [21]. A study from [22] involved twelve countries in the Caribbean and macro-financial data. A study from [23] involved eleven cities in the US and focused on how 137 amenities factors influence pricing.…”
Section: Literature Reviewmentioning
confidence: 99%